Investigating the performance of seals using photoelastic experimental hybrid method and finite element analysis - Bruno R. MOSE; Dong-Kil SHIN; Dong-Chul SHIN (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2017)
In this paper, performance behavior of seals under compression and various hydraulic pressures were investigated. Two approaches (experimental and numerical) have been used. It was found that significant improvements in seal performance can be achieved by carefully combining rectangular and circular profiles into one seal. The folding mechanism at the step of the seal with H1/H2 =2.5 was found to contribute the seal's best performance. Further, for each loading condition, contact stresses were greater than the applied hydraulic pressures. This important sealing criterion confirmed that the new seal geometry has good sealing capability. Contrary to previous studies, contact stresses were found to possess a non Hertzian profile. By measuring contact lengths using a video microscope, the seal with new geometry recorded higher contact lengths compared with seals having circular profile. The fringe patterns and deformation behavior from numerical models showed remarkable similarity with experimental results.